Names of hydroids (Cnidaria, Hydrozoa) established by Charles McLean Fraser (1872–1946), excluding those from Allan Hancock Expeditions - Calder, Dale R.; Choong, Henry H.c. (Zootaxa, 2018)
An account is given of the names of families, genera, and species of hydroids established by C.M. Fraser of Canada, excluding those from Allan Hancock Pacific Expeditions and the Allan Hancock Caribbean Sea Expedition. The names of four families, 11 genera, and 101 species are attributed to him in this work, complementing those of another two genera and 164 species described by Fraser in various Allan Hancock publications. Information is provided on type localities of his new species, on locations and kinds of type material in existence, where known, and on the current taxonomic status of families, genera, and species described by him in works reviewed herein. Two replacement names (Thuiaria geniculata Fraser, 1918a and Salacia fraseri Calder, 1991) exist for Thuiaria distans Fraser, 1914a (not Thuiaria distans Allman, 1877). The widely overlooked senior synonym, T. geniculata, is recognized as the valid name of the species. Diphasia alta nom. nov. is proposed as a new replacement name for the permanently invalid junior primary homonym Diphasia robusta Fraser, 1943a (not D. attenuata robusta Billard, 1924). In addition, Cryptolaria crassa nom. nov. is proposed as a new replacement name for the junior secondary homonym Cryptolaria rigida (Fraser, 1948) [not C. rigida (Fraser, 1940a)]. Lectotypes have been designated for 47 of the species to establish objective standards for application of their names. Corymorpha adventitia Fraser, 1941b, from the Pacific coast of Panama, is assigned to Ralpharia Watson, 1980, as R. adventitia. No type specimens are known to exist for seven of the species considered, including one holotype (of Hebella eximia Fraser, 1944a) missing from its bottle. Particular attention has been paid to dating and chronology of the 51 publications of Fraser covered in this work. Earlier bibliographic errors are corrected, most notably establishing that the book Distribution and relationship in American hydroids was published in early 1947 rather than 1946 as per the title page.